The Moderation Effect of Allowance for Impairment of Credit Losses Toward Credit Growth and Profitability - Angga Nugraha (PT. EQUATOR SINAR AKADEMIA, 2022)
This study aims to examine the Allowance For Impairment Of Credit Losses in moderating the relationship between credit growth and non-performing loans to profitability. The population in this study are all commercial banks listed on the Indonesia Stock Exchange in 2019-2022. purposive sampling is the sampling method used in this study. data were analyzed by PLS-SEM. The test results show that credit has an effect on ROA while NPL does not. Allowance For Impairment Of Credit Losses moderates the relationship between NPL and ROA.